Bunuel wrote:

What is the value of x - y?

(1) (x + y)^2 = 4xy --> \(x^2+2xy+y^2=4xy\) --> \(x^2-2xy+y^2=0\) --> \((x-y)^2=0\) --> \(x-y=0\). Sufficient.

(2) x^2 - y^2 = 0 --> \((x-y)(x+y)=0\) --> \(x-y=0\) or \(x+y=0\). Not sufficient.

Answer: A.

Hope it's clear.

Hi,

I am just curious as to why statement 2 isnt sufficient: bcos from statement 2: x-y=0 (i know x+y=0 too but question didn't ask about x+y so I am thinking its answer is irrelevant and that the important question of x-y has been answered). Besides its not like x-y is giving us two answers.

What am I missing here?